CARTs on the road for myeloma - Maus, Marcela V. (2014)
Chimeric antigen receptors re-direct T cells to surface antigens. Discovery and validation of appropriate target antigens expands the possible indications for CAR-T cells. CS1 is expressed at high levels by multiple myeloma cells, but also to some extent on other lymphocytes. CS1 may be a viable target for CAR-T cells in multiple myeloma.